The investigation of intrapsychological processes of primary school teachers with regards to the use of Corporal Punishment: A Case Study - Arosi, Sinovuyo Luyanda (University of the Witwatersrand, Johannesburg, 2023)
Corporal punishment has been legally abolished and identified as having detrimental effects on the psychological well-being of children. The reconstruction of external events and interpersonal states, such as corporal punishment, into intrapsychological and interpsychological activity, demonstrates the vulnerability of humans. Primary school teachers are instrumental in the development of higher mental functioning and the mental transformation of young children. The current study examined the intrapersonal processes of primary school teachers and their attitudes towards the use of corporal punishment when disciplining learners. A case study design was employed to explore teachers’ views on the abolishment of corporal punishment and the intermental, socio-cultural and cultural-historical mechanisms which inform their preference for corporal punishment. The teachers from a township school in the East of Johannesburg completed a demographic questionnaire and participated in focus group discussions and individual interviews. This qualitative data was collected using audio recordings which were transcribed and thematically analysed. Vygotsky’s sociocultural approach was used to understand the transformation of the human mind using cultural tools, namely, corporal punishment. Through the cultural-historical teachers’ meaning-making regarding the preference of corporal punishment in their context. The findings of this study suggest that the teachers in the case study school use and view corporal punishment through the lens of an internalised good and abusive tool. Though some of the teachers express support for the abolition of corporal punishment, they currently use this discipline measure. The findings present a paradox that represents the internal state of ambivalence that exists within the participants. These findings suggest that this may contribute to the continued use of corporal punishment in the case study school.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Education (Educational Psychology), Department of Psychology, Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, Johannesburg, 2023.
Keywords: Corporal punishment; CHAT; Intrapsychological processes; South Africa; UCTD; SDG-3: Good health and well-being